Radiation induces acute and subacute vascular regression in a three-dimensional microvasculature model - Choi, Dong-Hee; Oh, Dongwoo; Na, Kyuhwan; Kim, Hyunho; Choi, Dongjin; Jung, Yong Hun; Ahn, Jinchul; Kim, Jaehoon; Kim, Chun-Ho; Chung, Seok (Frontiers in Oncology, 2023)
Radiation treatment is one of the most frequently used therapies in patients with cancer, employed in approximately half of all patients. However, the use of radiation therapy is limited by acute or chronic adverse effects and the failure to consider the tumor microenvironment. Blood vessels substantially contribute to radiation responses in both normal and tumor tissues. The present study employed a three-dimensional (3D) microvasculature-on-a-chip that mimics physiological blood vessels to determine the effect of radiation on blood vessels. This model represents radiation-induced pathophysiological effects on blood vessels in terms of cellular damage and structural and functional changes. DNA double-strand breaks (DSBs), apoptosis, and cell viability indicate cellular damage. Radiation-induced damage leads to a reduction in vascular structures, such as vascular area, branch length, branch number, junction number, and branch diameter; this phenomenon occurs in the mature vascular network and during neovascularization. Additionally, vasculature regression was demonstrated by staining the basement membrane and microfilaments. Radiation exposure could increase the blockage and permeability of the vascular network, indicating that radiation alters the function of blood vessels. Radiation suppressed blood vessel recovery and induced a loss of angiogenic ability, resulting in a network of irradiated vessels that failed to recover, deteriorating gradually. These findings demonstrate that this model is valuable for assessing radiation-induced 2 This is a provisional file, not the final typeset article vascular dysfunction and acute and chronic effects and can potentially improve radiotherapy efficiency.